MENINGKATKAN KEMAMPUAN KONSEP BILANGAN MELALUI MEDIA STIK ES KRIM PADA ANAK USIA 4 – 5 TAHUN DI PAUD EPTA PANDAU JAYA KECAMATAN SIAK HULU - Musdyarty, Dessy; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This type of research is a class act. According Suharsimi et al (2006) action research (PTK) is the research done in the classroom with the aim of improving the quality of teaching practices. In this case that is the subject of this study is children early childhood Epta Pandau Siak Hulu Selangor District totaling as many children as many as 19 people including 13 women and 6 men. The data was collected using observation and documentation. Based on the survey results revealed that 1) the ability to recognize the concept of the number of children aged 4-5 years in early childhood Epta Siak Hulu district Kampar before playing popsicle stick berkriteria less meaning in the classical or the general concept of the ability to know how many children have grown. After playing popsicle stick in the first cycle and the second berkriteria good means for classical or general ability to recognize the concept of the number of children has grown very well. 2) Play ice cream sticks can improve the ability to know the concept of the number of children aged 4-5 years in early childhood Epta Siak Hulu district of Kampar regency. 3 In the hypothesis testing that can be gained from an increase in each cycle. Where an increase in the ability to recognize the concept of the number obtained before taking action to increase the cycle of 12.9%. While the increase in the ability to recognize the concept of the number of the first cycle to the second cycle of 53.6%.Key Word: the concept of number , medium ice cream sticks